Anti-disturbance ultra-high performance concrete for wet joint cast-in-place and preparation method thereof
By using composite cement, internal curing aggregate and composite expansion agent in concrete, combined with polycarboxylic acid water reducing agent, the problem of poor shrinkage and bonding effect of joint concrete is solved, and high early strength and low shrinkage rate are achieved. Improve the disturbance resistance and construction quality of road and bridges.
Patent Information
- Application Number
- CN202411482782.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The existing joint concrete has large dry shrinkage and poor bonding effect, resulting in poor disturbance resistance and difficult to meet the design requirements of high load and longevity surfaces of road bridges, especially in sectional construction or assembly.
Use composite cement, composite blends and high-quality fine aggregates, combined with internal curing aggregates and composite expansion agents, use polycarboxylic acid water reducing agents and early emphasis coagulation admixtures to adjust the construction performance of concrete to achieve high early strength and low strength Shrinkage and moderate settling time reduce the impact of external disturbances on the construction of the bridge.
The high early strength and low shrinkage rate of ultra-high performance concrete are achieved, reducing the problem of concrete shrinkage and cracking, improving the structural quality and disturbance resistance of construction, and simplifying the construction process.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement-based building materials, and in particular to an ultra-high performance concrete for anti-disturbance wet joint cast-in-place and a preparation method thereof. Background Art
[0002] With the rapid development of logistics and transportation, road infrastructure such as highways and bridges are subject to increasingly heavy traffic loads, and the maintenance costs caused by defects are gradually increasing.
[0003] In order to meet the high-load and long-life surface design requirements of roads and bridges, UHPC has gradually been widely used in construction. Modern roads and bridges have large spans and long lengths, and often adopt segmented construction or assembly, so the treatment of joints is particularly critical.
[0004] Ordinary joint concrete has large shrinkage and poor bonding effect, resulting in poor anti-disturbance effect. It is urgent to develop a new type of ultra-high performance concrete for wet joints with early strength, good volume stability and moderate setting time. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides an ultra-high performance concrete for anti-disturbance wet joint cast-in-place, which realizes humidity control by adopting composite cement, composite admixtures, high-quality fine aggregate, and preparing internal curing aggregate, and inhibits concrete shrinkage by using composite expansion agent, and adjusts concrete construction performance by using special water reducing agent, and cooperates with the use of early strength setting admixture, so as to achieve high early strength, low shrinkage and consistent setting time of ultra-high performance concrete, and reduce the influence of external disturbance on road and bridge construction.
[0006] Specifically, the anti-disturbance wet joint cast-in-place ultra-high performance concrete of the present invention is composed of the following raw materials in parts by weight:
[0007] 540-560 parts of Portland cement, 200-220 parts of ferroaluminate cement, 150-200 parts of ultrafine fly ash, 120-180 parts of microsilica fume, 100-200 parts of internal curing aggregate, 700-900 parts of fine aggregate, 15-20 parts of active calcium oxide, 5-10 parts of active magnesium oxide, 24-30 parts of polycarboxylate water reducer, 0.1-0.3 parts of lithium carbonate, 1.8-2.2 parts of boric acid, 150-200 parts of steel fiber, and 290-350 parts of water.
[0008] The present invention adopts silicate cement and ferroaluminate cement as composite cement, which has certain micro-expansion characteristics. Ultrafine fly ash and microsilica powder have high activity, small particle size and large specific surface area. Active calcium oxide and active magnesium oxide are used as composite expansion agents. The cementitious material produces continuous compensatory shrinkage during the coagulation process and the hydration process after final setting.
[0009] Preferably, the internal curing aggregate preparation process is:
[0010] a. Mix 80-90 parts of porous silicate powder and 5-10 parts of sodium carbonate, heat and calcine, keep warm, and quench to obtain a modified porous silicate powder.
[0011] b. Mix 50-75 parts of steel slag powder, 15-35 parts of modified porous silicate powder, 8-15 parts of silicate cement, 2-5 parts of microsilica powder, and 0.03-0.05 parts of SAP particles to obtain powder.
[0012] c. Add 95-105 parts of powder to the drum granulator, slowly spray 18-25 parts of water, and rotate to granulate to obtain 2.36-4.75mm billets.
[0013] d. Carbonize and cure the blank, soak and cure it, and dry it.
[0014] The present invention prepares internal curing aggregate, achieves a balance between porosity and strength, cooperates with the water absorption, water retention and water release characteristics of SAP particles, realizes self-curing in the later curing process of ultra-high performance concrete, and reduces the shrinkage of concrete.
[0015] Preferably, the polycarboxylic acid water-reducing agent is polymerized with 10-15 parts of acrylic acid, 70-90 parts of methyl allyl alcohol polyoxyethylene ether, 3-8 parts of 2-acrylamide-2-methylpropane sulfonic acid, and 2-7 parts of cyclodextrin monomaleate as monomers.
[0016] The polycarboxylate water-reducing agent of the present invention can adjust the rheological properties of the slurry, maintain the fluidity of the concrete while improving the dispersion effect of the internal curing aggregate, and has a good synergistic effect with boric acid. For the cementitious material system of the present invention, it can prolong the initial setting time of the concrete while shortening the final setting time, and cooperate with lithium carbonate to achieve early strength of the concrete, thereby reducing the influence of external disturbances on road and bridge construction.
[0017] Preferably, the silicate cement is P·II52.5 cement, with a specific surface area of 380m 2 / kg.
[0018] Preferably, the specific surface area of the ultrafine fly ash is ≥1500m 2 / kg, 28d activity index ≥100%.
[0019] Preferably, the microsilica powder is single crystal microsilica powder with a specific surface area of ≥18000m 2 / kg, SiO2 content ≥96%.
[0020] Preferably, the steel fiber is a copper-plated straight steel fiber with a diameter of 0.21-0.23 mm and a length of 12-14 mm.
[0021] Preferably, in the process for preparing the internal curing aggregate, the porous silicate powder in step a is diatomaceous earth, containing SiO2 with a mass fraction of 88.95%, an average pore diameter of 56.2 nm, a particle size ≤0.075 mm, and a loss on ignition of 0.39%.
[0022] Preferably, in the internal curing aggregate preparation process, the temperature is raised to 900-1100° C. for calcination in step a, and the holding time is 1-2 hours.
[0023] Preferably, in the internal curing aggregate preparation process, the particle size of the SAP particles in step b is ≤0.15 mm.
[0024] Preferably, in the internal curing aggregate preparation process, in the carbonization curing in step d, the carbonization pressure is 0.1-0.5 MPa, the temperature is 20-24° C., the relative humidity is 50-70%, and the carbonization curing time is 24-48 h.
[0025] Preferably, in the internal curing aggregate preparation process, the immersion curing time in step d is 24-30 hours.
[0026] The present invention also relates to a method for preparing the above-mentioned ultra-high performance concrete for anti-disturbance wet joint cast-in-place, which specifically comprises the following steps:
[0027] 1) Weigh each raw material by weight,
[0028] 2) Add the internal curing aggregate and part of the water into the mixer to mix and pre-wet.
[0029] 3) Add silicate cement, ferroaluminate cement, ultrafine fly ash, microsilica powder, fine aggregate, activated calcium oxide, activated magnesium oxide to the mixer and mix evenly. Add steel fiber and mix evenly.
[0030] 4) Evenly mix the polycarboxylate water reducer, lithium carbonate, boric acid and the remaining water to obtain an admixture solution.
[0031] 5) Add the additive solution into the mixer and mix well to obtain slurry.
[0032] 6) The slurry is molded and cured.
[0033] The present invention has the following technical advantages:
[0034] 1. The ultra-high performance concrete of the present invention has a small total shrinkage and drying shrinkage, which can effectively reduce the problems of insufficient interface bonding strength caused by self-shrinkage during pouring and shrinkage cracking during later maintenance and operation.
[0035] 2. The present invention achieves ultra-high early strength of concrete by combining raw materials, and controls the difference between initial setting and final setting time of concrete, which is convenient for construction and structural quality after construction, and has high mechanical properties in the later stage.
[0036] 3. The invention is simple to construct, highly practical, can be used for wet joint cast-in-place construction, and has strong anti-disturbance capability. DETAILED DESCRIPTION
[0037] In order to characterize the technical effect of the present invention, concrete was prepared and its performance was tested. During the test, the silicate cement was P·Ⅱ52.5 cement with a specific surface area of 395m 2 / kg, the specific surface area of ultrafine fly ash is 1600m 2 / kg, 28d activity index is 105%, microsilica powder is single crystal microsilica powder, specific surface area is 18000m 2 / kg, SiO2 content is 96%, the steel fiber is copper-plated straight steel fiber, the diameter is 0.21-0.23mm, the length is 12-14mm, the porous silicate powder is diatomaceous earth powder from Linjiang City, Jilin Province, containing SiO2 mass fraction of 88.95%, average pore diameter of 56.2nm, particle size ≤0.075mm, and loss on ignition is 0.39%.
[0038] Example 1
[0039] Concrete, characterized in that it is composed of the following raw materials in parts by weight:
[0040] 560 parts of Portland cement, 210 parts of ferroaluminate cement, 170 parts of ultrafine fly ash, 140 parts of microsilica fume, 200 parts of internal curing aggregate, 800 parts of fine aggregate, 17 parts of active calcium oxide, 5 parts of active magnesium oxide, 28 parts of polycarboxylate water reducer, 0.2 parts of lithium carbonate, 1.9 parts of boric acid, 160 parts of steel fiber, 340 parts of water,
[0041] The internal curing aggregate preparation process is:
[0042] a. Mix 80 parts of porous silicate powder and 7 parts of sodium carbonate, heat to 1000℃ and calcine, keep warm for 1.5h, and cool rapidly to obtain modified porous silicate powder.
[0043] b. Mix 65 parts of steel slag powder, 25 parts of modified porous silicate powder, 12 parts of Portland cement, 3 parts of microsilica powder, and 0.05 parts of SAP particles to obtain a powder.
[0044] c. Add 100 parts of powder into the drum granulator, slowly spray in 25 parts of water, and rotate to granulate to obtain 2.36-4.75mm billets.
[0045] d. Carbonize and cure the blank for 24 hours in an environment with a pressure of 0.3MPa, a temperature of 20°C, and a relative humidity of 60%, soak and cure for 24 hours, and dry to obtain,
[0046] The polycarboxylic acid water reducer is polymerized with 15 parts of acrylic acid, 85 parts of methyl allyl alcohol polyoxyethylene ether, 5 parts of 2-acrylamide-2-methylpropane sulfonic acid and 6 parts of cyclodextrin monomaleate as monomers.
[0047] The initial setting time of concrete was 68 minutes, the final setting time was 115 minutes, the 1-day compressive strength was 97.8 MPa, the 3-day compressive strength was 131.2 MPa, the 28-day compressive strength was 149.6 MPa, and the total shrinkage was 450×10 -6 , shrinkage 251×10 -6 .
[0048] Example 2
[0049] Concrete, characterized in that it is composed of the following raw materials in parts by weight:
[0050] 560 parts of Portland cement, 200 parts of ferroaluminate cement, 170 parts of ultrafine fly ash, 160 parts of microsilica fume, 190 parts of internal curing aggregate, 810 parts of fine aggregate, 18 parts of active calcium oxide, 7 parts of active magnesium oxide, 30 parts of polycarboxylate water reducer, 0.2 parts of lithium carbonate, 2.1 parts of boric acid, 170 parts of steel fiber, 340 parts of water,
[0051] The internal curing aggregate preparation process is:
[0052] a. Mix 90 parts of porous silicate powder and 10 parts of sodium carbonate, heat to 1000°C for calcination, keep warm for 1.5h, and quench to obtain modified porous silicate powder.
[0053] b. Mix 70 parts of steel slag powder, 30 parts of modified porous silicate powder, 8 parts of silicate cement, 3 parts of microsilica powder and 0.05 parts of SAP particles to obtain a powder.
[0054] c. Add 105 parts of powder to the drum granulator, slowly spray in 22 parts of water, and rotate to granulate to obtain 2.36-4.75 mm billets.
[0055] d. Carbonize and cure the blank for 24 hours in an environment with a pressure of 0.3MPa, a temperature of 20°C, and a relative humidity of 60%, soak and cure for 24 hours, and dry to obtain,
[0056] The polycarboxylic acid water reducer is prepared by polymerizing 13 parts of acrylic acid, 90 parts of methyl allyl alcohol polyoxyethylene ether, 7 parts of 2-acrylamide-2-methylpropane sulfonic acid and 4 parts of cyclodextrin monomaleate as monomers.
[0057] The initial setting time of concrete was 80 min, the final setting time was 133 min, the 1-day compressive strength was 98.1 MPa, the 3-day compressive strength was 136.4 MPa, the 28-day compressive strength was 152.3 MPa, and the total shrinkage was 443×10 -6, shrinkage 246×10 -6 .
[0058] Comparative Example 1
[0059] Concrete, characterized in that it is composed of the following raw materials in parts by weight:
[0060] 560 parts of Portland cement, 210 parts of ferroaluminate cement, 170 parts of ultrafine fly ash, 140 parts of microsilica powder, 1000 parts of fine aggregate, 17 parts of active calcium oxide, 5 parts of active magnesium oxide, 28 parts of polycarboxylate water reducer, 0.2 parts of lithium carbonate, 1.9 parts of boric acid, 160 parts of steel fiber, 340 parts of water,
[0061] The polycarboxylic acid water reducer is polymerized with 15 parts of acrylic acid, 85 parts of methyl allyl alcohol polyoxyethylene ether, 5 parts of 2-acrylamide-2-methylpropane sulfonic acid and 6 parts of cyclodextrin monomaleate as monomers.
[0062] The initial setting time of concrete was 75 minutes, the final setting time was 133 minutes, the 1-day compressive strength was 94.5 MPa, the 3-day compressive strength was 102.4 MPa, the 28-day compressive strength was 119.7 MPa, and the total shrinkage was 1340×10 -6 , shrinkage 760×10 -6 .
[0063] Comparative Example 2
[0064] Concrete, characterized in that it is composed of the following raw materials in parts by weight:
[0065] 560 parts of Portland cement, 210 parts of ferroaluminate cement, 170 parts of ultrafine fly ash, 140 parts of microsilica fume, 190 parts of 2.36-4.75mm pottery sand, 5 parts of SAP particles, 800 parts of fine aggregate, 17 parts of active calcium oxide, 5 parts of active magnesium oxide, 28 parts of polycarboxylate water reducer, 0.2 parts of lithium carbonate, 1.9 parts of boric acid, 160 parts of steel fiber, 340 parts of water,
[0066] The polycarboxylic acid water reducer is polymerized with 15 parts of acrylic acid, 85 parts of methyl allyl alcohol polyoxyethylene ether, 5 parts of 2-acrylamide-2-methylpropane sulfonic acid and 6 parts of cyclodextrin monomaleate as monomers.
[0067] The test results show that the initial setting time of concrete is 69 minutes, the final setting time is 128 minutes, the 1-day compressive strength is 81.7 MPa, the 3-day compressive strength is 92.4 MPa, the 28-day compressive strength is 109.0 MPa, and the total shrinkage is 910×10 -6 , shrinkage 495×10 -6 .
[0068] Comparative Example 3
[0069] Concrete, characterized in that it is composed of the following raw materials in parts by weight:
[0070] 560 parts of Portland cement, 210 parts of ferroaluminate cement, 170 parts of ultrafine fly ash, 140 parts of microsilica fume, 200 parts of internal curing aggregate, 800 parts of fine aggregate, 17 parts of active calcium oxide, 5 parts of active magnesium oxide, 28 parts of polycarboxylate water reducer, 0.2 parts of lithium carbonate, 1.9 parts of boric acid, 160 parts of steel fiber, 340 parts of water,
[0071] The internal curing aggregate preparation process is:
[0072] a. Mix 80 parts of porous silicate powder and 7 parts of sodium carbonate, heat to 1000℃ and calcine, keep warm for 1.5h, and cool rapidly to obtain modified porous silicate powder.
[0073] b. Mix 65 parts of steel slag powder, 25 parts of modified porous silicate powder, 12 parts of Portland cement, 3 parts of microsilica powder, and 0.05 parts of SAP particles to obtain a powder.
[0074] c. Add 100 parts of powder into the drum granulator, slowly spray in 25 parts of water, and rotate to granulate to obtain 2.36-4.75mm billets.
[0075] d. Carbonize and cure the blank for 24 hours in an environment with a pressure of 0.3MPa, a temperature of 20°C, and a relative humidity of 60%, soak and cure for 24 hours, and dry to obtain,
[0076] The polycarboxylic acid water reducer is prepared by polymerizing 15 parts of acrylic acid, 90 parts of methyl allyl alcohol polyoxyethylene ether and 7 parts of 2-acrylamide-2-methylpropane sulfonic acid as monomers.
[0077] The initial setting time of concrete was 122 minutes, the final setting time was 215 minutes, the 1-day compressive strength was 87.6 MPa, the 3-day compressive strength was 113.2 MPa, the 28-day compressive strength was 122.7 MPa, and the total shrinkage was 760×10 -6 , shrinkage 435×10 -6 .
[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. An ultra-high performance concrete for anti-disturbance wet joint casting, characterized in that: It is composed of the following raw materials in parts by weight: 540-560 parts of silicate cement, 200-220 parts of ferroaluminate cement, 150-200 parts of ultrafine fly ash, 120-180 parts of microsilica fume, 100-200 parts of internal curing aggregate, 700-900 parts of fine aggregate, 15-20 parts of active calcium oxide, 5-10 parts of active magnesium oxide, 24-30 parts of polycarboxylate water reducer, 0.1-0.3 parts of lithium carbonate, 1.8-2.2 parts of boric acid, 150-200 parts of steel fiber, 290-350 parts of water, The internal curing aggregate preparation process is: a. Mix 80-90 parts of porous silicate powder and 5-10 parts of sodium carbonate, heat and calcine, keep warm, and quench to obtain a modified porous silicate powder. b. Mix 50-75 parts of steel slag powder, 15-35 parts of modified porous silicate powder, 8-15 parts of silicate cement, 2-5 parts of microsilica powder, and 0.03-0.05 parts of SAP particles to obtain powder. c. Add 95-105 parts of powder to the drum granulator, slowly spray 18-25 parts of water, and rotate to granulate to obtain 2.36-4.75mm billets. d. Carbonize and cure the blank, soak and cure it, and dry it to obtain: The polycarboxylic acid water reducer is prepared by polymerizing 10-15 parts of acrylic acid, 70-90 parts of methyl allyl alcohol polyoxyethylene ether, 3-8 parts of 2-acrylamide-2-methylpropane sulfonic acid and 2-7 parts of cyclodextrin monomaleate as monomers.
2. The ultra-high performance concrete for anti-disturbance wet joint cast-in-place according to claim 1, characterized in that: The silicate cement is P·Ⅱ52.5 cement, with a specific surface area of 380m 2 / kg.
3. The ultra-high performance concrete for anti-disturbance wet joint cast-in-place according to claim 1, characterized in that: The specific surface area of the ultrafine fly ash is ≥1500m 2 / kg, 28d activity index ≥100%.
4. The ultra-high performance concrete for anti-disturbance wet joint cast-in-place according to claim 1, characterized in that: The microsilica powder is single crystal microsilica powder with a specific surface area of ≥18000m 2 / kg, SiO2 content ≥96%.
5. The ultra-high performance concrete for cast-in-place anti-disturbance wet joints according to claim 1, characterized in that: The steel fiber is a copper-plated straight steel fiber with a diameter of 0.21-0.23 mm and a length of 12-14 mm.
6. The ultra-high performance concrete for cast-in-place anti-disturbance wet joints according to claim 1, characterized in that: In the internal curing aggregate preparation process, the porous silicate powder in step a is diatomaceous earth, containing SiO2 by mass fraction of 88.95%, an average pore diameter of 56.2nm, a particle size of ≤0.075mm, and a loss on ignition of 0.39%.
7. The ultra-high performance concrete for cast-in-place anti-disturbance wet joints according to claim 1, characterized in that: In the internal curing aggregate preparation process, the particle size of the SAP particles in step b is ≤0.15 mm.
8. The ultra-high performance concrete for cast-in-place anti-disturbance wet joints according to claim 1, characterized in that: In the internal curing aggregate preparation process, in step d, the carbonization pressure in the carbonization curing is 0.1-0.5 MPa, the temperature is 20-24° C., the relative humidity is 50-70%, and the carbonization curing time is 24-48 hours.
9. The ultra-high performance concrete for cast-in-place anti-disturbance wet joints according to claim 1, characterized in that: In the internal curing aggregate preparation process, the immersion curing time in step d is 24-30 hours.
10. The method for preparing the ultra-high performance concrete for anti-disturbance wet joint cast-in-place according to any one of claims 1 to 9, characterized in that: The steps include: 1) Weigh each raw material by weight, 2) Add the internal curing aggregate and part of the water into the mixer to mix and pre-wet. 3) Add silicate cement, ferroaluminate cement, ultrafine fly ash, microsilica powder, fine aggregate, activated calcium oxide, activated magnesium oxide to the mixer and mix evenly. Add steel fiber and mix evenly. 4) Evenly mix the polycarboxylate water reducer, lithium carbonate, boric acid and the remaining water to obtain an admixture solution. 5) Add the additive solution into the mixer and mix well to obtain slurry. 6) The slurry is molded and cured.
Citation Information
Patent Citations
Water absorbent swelling resin aggregate concrete and preparation method thereof
CN103332902A
Method for preparing high-strength silicate cement product
CN104628341A
Low-viscosity low-shrinkage ultra-high performance concrete repairing material and using method thereof
CN113185243A
Ultra-high performance concrete based on internal curing of recycled fine aggregate and preparation method of ultra-high performance concrete
CN113816696A
Preparation of submicron high-water-retention water-absorption internally-cured microspheres and method for inhibiting early shrinkage of ultra-high performance concrete by using submicron high-water-retention water-absorption internally-cured microspheres
CN118344522A